Study of head and chest growth and their equalization in Churachandpur, Manipur during the first year of life - Ngaithianven, Evelyn (International Journal Of Community Medicine And Public Health, 2022)
Background: The study of head and chest circumferences and the subsequent age at equalization, when studying infant growth, played a vital role in a community as it helps in identifying those who are susceptible to nutritional issues. Keeping in view the importance, a journey was embarked upon with the object of finding out the growth of head and chest circumferences as well as their age of equalization among the tribal infants in Churachandpur, Manipur. Methods: Using longitudinal setting, infants taken into account were full term born and measurements were recorded within 24 hours of birth from maternity clinics and hospitals in Churachandpur. The growth pattern of head and chest circumferences were measured independently from birth till the child attained 1 year of age at monthly interval following standard techniques given by Weiner and Lourie by using a narrow, flexible, non-stretch steel tape calibrated in centimetres. Results: Observation of earlier equalization of head and chest circumferences is recorded among the tribal group studied. After the observation of equalization, chest circumference remains larger than head circumference in both sexes throughout the first year of life, which signifies a good growth among the infant group studied. Conclusions: It can be recommended from the present study the use of head and chest circumference for identifying vulnerable infant/children from their nutritional standpoint in any kind of settings as it is easily accessible and cost effective. The present study shows a positive secular trend when compared with other available literatures.